Incidence of mycobiota and aflatoxin B1 in Algerian feed. (29th March 2022) - Bouti, Karima; Mimoune, Nouara Ait; Mokrane, Salim; Djemouai, Nadjette; Verheecke-Vaessen, Carol; Mathieu, Florence; Riba, Amar
The presence of fungi and aflatoxin B1 (AFB1 ) in 101 animal feed samples randomly collected from different vendors and factories in Algeria was investigated. For fungi, the main genera isolated were Aspergillus, Penicillium and Fusarium . Furthermore, the 459 strains of Aspergillus section Flavi were screened for their ability to produce aflatoxins and cyclopiazonic acid (CPA). 49% of the strains produced AFB1 while 74.5% were cyclopiazonic acid producers. The highest incidence of aflatoxigenic strains was recorded in maize (61%) and ground poultry feed (60%). The presence of AFB1 in 101 feed samples was evaluated using HPLC-FLD. The obtained data showed that 36.6% of samples were contaminated in the range of 0.34 to 171.06 μg/kg. Six samples exceeded the Algerian maximum limit of 20 μg/kg for AFB1 . This study highlights the potential presence of aflatoxigenic strains belonging to section Flavi and AFB1 in animal feed in Algeria, strategic information for the Algerian policymakers.